Series termination of single-ended LVCMOS signals - Seheda, Oleh; Nazarkevych, Ihor (Видавництво Львівської політехніки, 2023)
For synchronous signals with fast edges traces on printed circuit boards are transmission lines, not just conductor connections. If the length of the PCB trace exceeds certain values, it is necessary to match its impedance with the signal source and/or receiver. Impedance mismatches would bring signal reflections from the source to the receiver and back through the transmission line. Such reflection or distortion of the signal is called "echo" or "ringing". It is shown in emissions and irregularities of the waveform, especially the rise and fall edge. In this article, practical guidelines for sequential termination of one-way signals are considered that would resolve such effects. The simulations were done for LVCMOS signals [1].
Keywords: Single-ended signals; synchronous signals; impedance matching; rise/fall time; transmission line